An Artificial Soft Tissue Made of Nano-Alginate Polymer Using Bioxfab 3D Bioprinter for Treatment of Injuries - Kimia Salimi; Sajedeh Eghbali; Amir Jasemi; Reza Shokrani Foroushani; Hamed Joneidi Yekta; Mehran Latifi; Saeed Saber-Samandari; Amirsalar Khandan (Nanochemistry Research, 2020)
Some pulsed tissues are replaced with non-pulsed damaged tissue, which jeopardizes heart function after a heart attack. The restoration is performed by a patch tissue to repair defective tissues. It is supposed to attach to the outside of the heart and connect to the wounded area. The above patch is made of a conductive polymer on which a separate electrical polymer called "alginate" through a process called 3D bioprinter. The mechanism of the following patch for biological and cell behavior has to be investigated. Besides, we explain the results of the combination of these polymers with natural and synthetic polymer composites. As a natural and biological soft patch for cardiovascular disease (CVD) the adhesion of cells to patch is more efficient and important. In this study, we used a novel technique to print sodium alginate for CVD problems with soft hydrogel patch loading with the restorative drug. In other words, by producing soft tissue patches, researchers and clinical surgeons can obtain more desirable properties made of natural and synthetic polymer composites for the treatment of heart disease. In this study, four CVD patches fabricated using 3D bioprinter X4bioFab with various amounts of drug on their surfaces containing 2%, 4%, 6%, and 8%. The obtained values for mechanical and biological performance present proper features for the sample containing a 6% drug. The results indicated the prepared patch can be a suitable candidate for heart disease with sufficient cell attachment after a while.